Risk Factors for Progression of Carotid Intima-Media Thickness and Total Plaque Area A 13-Year Follow-Up Study: The Tromsø Study - Herder, Marit; Johnsen, Stein Harald; Arntzen, Kjell Arne; Mathiesen, Ellisiv B. (Stroke, 2012)
This article is part of Marit Herder's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5723 Data on risk factors for progression of intima-media thickness (IMT) and plaque are scarce. The objective was to determine long-term risk factors for total plaque area (TPA) and IMT as well as risk factors for progression (ΔTPA and ΔIMT). Subjects were 1307 men and 1436 women who participated in a longitudinal population-based study with ultrasound examination of the right carotid artery at baseline and after 13 years of follow-up. Total cholesterol, high-density lipoprotein cholesterol, blood pressure, body mass index, and information about smoking habits, prevalent diabetes, and cardiovascular disease were obtained at baseline. Carotid atherosclerosis was assessed as TPA and mean IMT of plaque-free segments of the common carotid artery. Associations between z-scores of risk factors and carotid atherosclerosis were assessed in multiple linear regression models. In multivariable models, total cholesterol, systolic blood pressure, and smoking were stronger predictors of follow-up TPA than of IMT, whereas sex and age were stronger predictors of IMT. Total cholesterol (standardized β=0.081), systolic blood pressure (standardized β=0.062), and smoking (standardized β=0.107) were significant predictors of ΔTPA, whereas only total cholesterol (standardized β=0.084) was an independent predictor of ΔIMT. The variance explained by traditional cardiovascular risk factors was somewhat greater for TPA than for IMT. The cardiovascular risk factors total cholesterol, smoking, and systolic blood pressure were stronger long-term predictors of TPA and TPA progression than for IMT and IMT progression.